Growth and yield response of hybrid maize (Zea mays L.) to phosphorus levels in sandy loam soil of Chitwan Valley, Nepal - Baral, Bandhu Raj; Adhikari, Parbati; Shrestha, Jiban (International Journal of Environment, 2015)
To evaluate the phosphorus response on winter hybrid maize, a field experiment was conducted at farm land of National Maize Research Program, Rampur, Chitwan, Nepal on 2012 and 2013. Seven levels of Phosphorus i.e. 0, 20, 40, 60, 80, 100 and 120 kg P2O5 ha-1 were applied along with 160:40 kg N:K2O ha-1. The experiment was laid out in randomized complete block design with three replications. Hybrid maize RML 32 × RML 17 was used for this study. Analysis of variance showed that plant height (cm), dry matter accumulation (g), number of kernels per row, 1000 grain weight (g) and grain yield (ton ha-1) were significantly affected with Phosphorus level. The results showed that the trend of increment was positive for grain yield with increased P level from 0 to 80 kg P2O5 ha-1. The highest grain yield (10.77 ton ha-1) was measured when 120 kg P2O5 ha-1 is applied. It is concluded that 80 kg P2O5 ha-1 can be applied in winter season for hybrid maize RML-32 × RML-17 in Chitwan valley low land irrigated condition. Further studies are necessary on different soil types, seasons, management system and varieties to get more information about the most proper addition of P on maize. DOI: http://dx.doi.org/10.3126/ije.v4i2.12634 International Journal of Environment Vol.4(2) 2015: 147-156